Molecular cloning and primary structure of a Klebsiella pneumoniae pullulanase-encoding gene expressed in yeast - Janse, B. J. H.(Bernard Johannes Heinrich) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1993.